2017
DOI: 10.3390/s17122721
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Measurement of Nonlinearity of Laser Interferometer Based on Optical Frequency Tuning

Abstract: Abstract:A method for measuring the nonlinearity of laser interferometer using optical frequency tuning technique is presented in this paper. The basic principle of this method is to make the fractional part of an interference fringe change by tuning the laser frequency and determining the nonlinearity of interferometer by comparing the fractional fringe change measured by the interferometer to that calculated from the laser frequency change. An experimental interferometric system with a wavelength tunable las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In addition, we have shown that the outgoing direction of the complex harmonic coupling to the vacuum can be predicted precisely by using multiple reciprocal unit cells. The novel phenomenon could benefit any technique currently exploiting the conventional Doppler effect, such as the Doppler cooling of atomic gases, radar deception, invisibility cloaks, microstructure dual frequency interferometer 19 , 20 and so on. The technique is also applicable to systems with tunable sources of terahertz radiation and other frequency regions that are difficult to access.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have shown that the outgoing direction of the complex harmonic coupling to the vacuum can be predicted precisely by using multiple reciprocal unit cells. The novel phenomenon could benefit any technique currently exploiting the conventional Doppler effect, such as the Doppler cooling of atomic gases, radar deception, invisibility cloaks, microstructure dual frequency interferometer 19 , 20 and so on. The technique is also applicable to systems with tunable sources of terahertz radiation and other frequency regions that are difficult to access.…”
Section: Discussionmentioning
confidence: 99%